Ghrelin Alleviates Spinal Cord Injury in Rats Via Its Anti-inflammatory Effects - (:unkn) unknown (TURKISH NEUROSURGICAL SOC, 2011)
AIM: Spinal cord injury (SCI) leads to an inflammatory response that generates substantial secondary damage within the tissue besides the primary damage. Ghrelin, 28 amino-acid peptide, has been shown to modulate the release of proinflammatory cytokines and exert anti-inflammatory effects. The aim of the current study was to investigate the anti-inflammatory effects of ghrelin, in a rat model of SCI. MATERIAL and METHODS: Wistar albino rats were divided as control, SCI, and ghrelin-treated (10 mu g/kg/day, ip) SCI groups. In order to induce SCI, a standard weight-drop method that induced a moderately severe injury (100 g/cm force) at T10, was used. Injured animals were given either ghrelin or saline 15 min post-injury. RESULTS: In plasma samples, neuron-specific enolase (NSE) and S-100 beta protein levels were evaluated. Spinal cord samples were taken for histological examination or determination of myeloperoxidase (MPO) activity and DNA fragmentation. SCI caused significant increases in plasma NSE and S-100 beta levels and tissue MPO activity and DNA damage. On the other hand, ghrelin treatment improved histological findings as well as biochemical parameters while it failed to improve the impairment of the neurological functions due to SCI. CONCLUSION: The present study suggests that ghrelin could reduce SCI-induced oxidative stress and exert anti-inflammatory effects in the spinal cord following trauma.
Keywords: Ghrelin; Spinal cord injury; Neuroprotective; Rat; NEURON-SPECIFIC ENOLASE; BRAIN-DAMAGE; CELL-DEATH; FUNCTIONAL RECOVERY; ENDOTHELIAL-CELLS; ACYLATED PEPTIDE; OXIDATIVE STRESS; NERVOUS-SYSTEM; ORGAN INJURY; MOUSE MODEL